Composite mixed ionic-electronic conducting ceramic for intermediate temperature oxygen transport membrane. (August 2017) - Liao, Ming-Wei; Lin, Tai-Nan; Kao, Wei-Xin; Yeh, Chun-Yen; Chen, Yu-Ming; Kuo, Hong-Yi
Abstract: The dense ceramic substrate formed by a mixed ionic-electronic conducting (MIEC) material can be used as an oxygen transport membrane (OTM), enabling the transport of high flux oxygen with certain selectivity and gas separation at high temperatures (800 ~ 900 °C). In recent years, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3−δ (BSCF) has been reported to be a promising MIEC material for oxygen permeation due to its relatively high oxygen ion conductivity at high temperatures. However, the catalytic efficiency of BSCF is relatively low among the MIEC materials, resulting in the dramatic decrease of oxygen permeation at temperatures below 800 °C. In the present study, a composite MIEC ceramic consisting of a BSCF substrate and the catalytic La0.6 Sr0.4 Co0.2 Fe0.8 O3−δ (LSCF) layer has been proposed. A simple method of laser surface melting is executed to fabricate the composite oxygen transport membrane. The scanning electron microscope (SEM) investigations show that LSCF powders can be well-adherent to the BSCF surface after laser scanning melting process. The oxygen permeation flux reaches 0.5 ml min −1  cm −2 for pure BSCF membrane with thickness of 420 µm, while the BSCF membrane substrate with laser scanning LSCF exhibits substantial improvement on oxygen permeation up to 60% at 700 °C. The result suggests that the composite MIEC ceramic has significant potential for intermediate temperature oxygen transport membrane.